2019
DOI: 10.1590/0074-02760190017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxicity of nitroimidazoles as a tool in the search of new trypanocidal agents

Abstract: BACKGROUND Only benznidazole (Bnz) (1) and nifurtimox (Nfx) (2) are licensed for the treatment of Chagas disease although their safety and efficacy profile are far from ideal. Farmanguinhos from Fiocruz has developed seven nitroimidazole compounds (4-10) analogs of megazol (3). OBJECTIVES To evaluate whether the genotoxic effect of 3 was abolished in the seven nitroimidazoles (4-10) analogs using the in vitro alkaline comet assay (CA) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
5
0
6
Order By: Relevance
“…This disease is transmitted mainly by the bite of triatomines, but can also be transmitted congenitally, by transplants, blood transfusions, among other forms 1,7 . The only drugs approved by the WHO for its treatment are two nitroaromatic compounds: nifurtimox and benznidazole (BNZ), which are effective if they are administered at the onset of the infection; however, it has been reported that their effectiveness decreases and their toxicity increases in long‐term treatments, which makes them banned in many countries 1,2,8–10 . Such toxicity relates to the formation of free radicals generated by the reduction of the nitro group, which puts the parasite under oxidative stress and causes its death, but also causes damage to human cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease is transmitted mainly by the bite of triatomines, but can also be transmitted congenitally, by transplants, blood transfusions, among other forms 1,7 . The only drugs approved by the WHO for its treatment are two nitroaromatic compounds: nifurtimox and benznidazole (BNZ), which are effective if they are administered at the onset of the infection; however, it has been reported that their effectiveness decreases and their toxicity increases in long‐term treatments, which makes them banned in many countries 1,2,8–10 . Such toxicity relates to the formation of free radicals generated by the reduction of the nitro group, which puts the parasite under oxidative stress and causes its death, but also causes damage to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…effective if they are administered at the onset of the infection; however, it has been reported that their effectiveness decreases and their toxicity increases in long-term treatments, which makes them banned in many countries. 1,2,[8][9][10] Such toxicity relates to the formation of free radicals generated by the reduction of the nitro group, which puts the parasite under oxidative stress and causes its death, but also causes damage to human cells. Nevertheless, in the literature it has been reported that the antichagasic effect of BNZ does not depend on the production of free radicals and can act against the parasite in different ways, so its main mechanism of action is still unknown.…”
mentioning
confidence: 99%
“…Actualmente, la Organización Mundial de la Salud la ha clasificado dentro de la lista de las enfermedades tropicales desatendidas más importantes del mundo, con presencia en 21 países de América Latina, como: Belice, Bolivia, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Guyana Francesa, Guatemala, Guyana, Honduras, Nicaragua, Panamá, Paraguay, Perú, Suriname, Uruguay, Venezuela, Argentina, Brasil, y México [WHO, 2022;DNDI, 2022], donde, estos últimos, ocupan los tres primeros lugares en relación al número de infectados [WHO, 2015]. Sin embargo, debido a la migración, la enfermedad de Chagas también se ha encontrado en otros países y continentes, como: Estados Unidos de Norteamérica (con aproximadamente 300,000 personas infectadas) [FDA, 2017], Canadá, Japón, Australia y diversos países europeos, con lo cual, se ha colocado como un importante problema de salud pública para el resto del mundo [WHO, 2022;DNDI, 2022;Von Trompowsky, 2019;Merlino, 2014].…”
Section: Antecedentes Tripanosomiasis Americanaunclassified
“…El benznidazol es un nitroimidazol que es fabricado por el Laboratorio Farmacéutico del Estado de Pernambuco (de Brasil), por el Laboratorio Elea (de Argentina) y por Chemo Research, S. L. (de España) [Von Trompowsky, 2019;FDA, 2017]. Su acción está dada por diferentes rutas, las cuales tienen efecto sobre la síntesis del ácido desoxirribonucleico (DNA, por sus siglas en inglés) del parásito Trypanosoma cruzi.…”
Section: Antecedentes Tripanosomiasis Americanaunclassified
See 1 more Smart Citation